Meningkatkan Sikap Sosial Peserta Didik Melalui Layanan Bimbingan Klasikal Pada Masa New Normal - Coiroel Umi (Konseling Edukasi : Journal of Guidance and Counseling, 2022)
Improving Students' Social Attitudes Through Classical Guidance Services During the New Normal Period. This study aims to improve students' social attitudes using classical guidance, so that with a good understanding of social attitudes students can adjust to new normal conditions. The subjects in the study were class VIII F students of SMP Negeri 2 Blitar in the 2021/2022 academic year, totaling 31 consisting of 15 males and 16 females. Subjects were taken through a purposive sampling procedure. This action research is planned in two cycles, where in the cycle stage, two meetings are conducted. The type of research is Classroom Action Research in the field of Guidance and Counseling, namely by examining and reporting problems related to the social attitudes of students in schools with comparative descriptive analysis methods. The results of the comparative descriptive analysis showed that the social attitudes of students in the initial conditions, cycle I and cycle II experienced significant changes. This is shown in the initial data acquisition only 10 students (31.4%) have good social attitudes, but in the second cycle after the post test data obtained 26 students (83.9%) have good social attitudes. This study proves that classical guidance services are able to improve the social attitudes of VIII F students of SMP Negeri 2 for the 2021/2022 academic year..Keywords: Social Attitude, Classical Guidance, New Normal